Dural arteriovenous fistula causing reversible cognitive impairment. Issue 1 (18th August 2022) - Alexandratou, Anna; Mah, Yee; Ramsey, Deborah; Kandasamy, Naga; Tolias, Christos M; Gadapa, Naveen; Ankolekar, Sandeep
Abstract : A previously independent 82-year-old woman presented with 5 months of worsening confusion, mobility and cognitive decline, with deficits in orientation, language and executive function. A cerebral dural arteriovenous fistula was identified and successfully embolised, after which her cognitive ability and independence dramatically improved. Although rare, a dural arteriovenous fistula may mimic a rapidly progressive dementia, but its early recognition and treatment can completely reverse the dementia.